Retailers' behavioral factors towards Goods and Services Tax (GST) compliance: sociological and psychological approach study / Norhasliza Zainan ... [et al.] - Zainan, Norhasliza; Md Noor, Rohaya; Omar, Normah; Abd Aziz, Roszainun; Sanusi, Soliha (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2017)
The study attempts to investigate the relationship of goods and services tax (GST) compliance among retailers in Malaysia during the initial stage of GST implementation in Malaysia. Using the sociological and psychological approach, a total of 500 survey questionnaires were distributed during GST workshops conducted by the tax authority. Multiple regressions were employed to examine the relationship between behavioral factors: tax knowledge, perceived tax complexity and perceived tax fairness and GST compliance. The statistical results found that 77.7% of the identifying behavioral factors explained to the level of GST compliance The findings disclosed that tax knowledge, perceived tax complexity and perceived tax fairness were significantly and positively affect GST compliance Thus, the result of the study could possibly contribute to the body of knowledge in lieu of GST compliance, as well as being an input to the tax authority that tax education program is important and effective mechanism to enhance the retailers' understanding of their GST obligations and compliance level.